2013
DOI: 10.2478/orga-2013-0027
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Entrepreneurial Curiosity and Entrepreneurial Self-efficacy: a Multi-Country Empirical Validation

Abstract: The main purpose of this paper is to present empirical analysis of the relation between entrepreneurial curiosity and entrepreneurial self-efficacy. a detailed literature review in a broad field of entrepreneurship, narrow field of entrepreneurship psychology, and organizational sciences revealed, at one hand different connections between determinants influencing entrepreneurs, and latest scientific research trends on the other hand. although the significance of curiosity in motivating and learning has receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 77 publications
(64 reference statements)
1
22
0
Order By: Relevance
“…Entrepreneurial curiosity is an interest in novelties or observations of society and a tendency to search for answers that indicate which demands should be met and it also represents guidance and competitive advantages for entrepreneurs relative to the competition (Jeraj and Marič, 2013a). Entrepreneurial curiosity is awake, when an entrepreneur is facing different stimulus related to the entrepreneurship in the environment (Jeraj and Prodan 2010).…”
Section: Entrepreneurial Curiositymentioning
confidence: 99%
See 1 more Smart Citation
“…Entrepreneurial curiosity is an interest in novelties or observations of society and a tendency to search for answers that indicate which demands should be met and it also represents guidance and competitive advantages for entrepreneurs relative to the competition (Jeraj and Marič, 2013a). Entrepreneurial curiosity is awake, when an entrepreneur is facing different stimulus related to the entrepreneurship in the environment (Jeraj and Prodan 2010).…”
Section: Entrepreneurial Curiositymentioning
confidence: 99%
“…On the other site entrepreneurial curiosity was connected to entrepreneurial self-efficacy (Jeraj and Marič, 2013a); to openness and firm growth (Jeraj, 2014). Since both researched constructs in this paper, entrepreneurial curiosity and innovativeness are important elements of entrepreneurship and both were connected to other entrepreneurship parts.…”
Section: Introductionmentioning
confidence: 99%
“…Another study of Jeraj and Marič (2013a) indicated positive relationship between entrepreneurial curiosity and entrepreneurial self-efficacy measured on an international sample of entrepreneurs from Slovenia and USA, where was entrepreneurial curiosity, as also entrepreneurial selfefficacy a good predictor for entrepreneurial intentions. Further, on the one hand Luthans and Youssef (2004) suggest that individuals possessing the combination of selfefficacy, optimism, hope, and resiliency tend to be endowed with high levels of psychological capital, on the other hand Jensen and Luthans (2006) studied the link between entrepreneurs' positive psychological capital and leadership approach Marič et al, 2013), which was found as grounded.…”
Section: Entrepreneurial Curiosity and Optimismmentioning
confidence: 99%
“…Entrepreneurial curiosity is an interest in novelties or observations of society and a tendency to search for answers that indicate which demands should be met and it represents guidance and competitive advantages for entrepreneurs relative to the competition (Jeraj and Marič, 2013a). Entrepreneurial curiosity is awake, when an entrepreneur is facing different stimulus related to the entrepreneurship in the environment (Jeraj and Prodan 2010).…”
Section: Entrepreneurial Curiosity and Optimismmentioning
confidence: 99%
See 1 more Smart Citation